Cooperation of C/EBP family proteins and chromatin remodeling proteins is essential for termination of liver regeneration. Issue 1 (20th November 2014) - Jin, Jingling; Hong, Il‐Hwa; Lewis, Kyle; Iakova, Polina; Breaux, Meghan; Jiang, Yanjun; Sullivan, Emily; Jawanmardi, Nicole; Timchenko, Lubov; Timchenko, Nikolai A.
<x xml:space="preserve">Abstract</x> Liver cancer is the fifth most common cancer. A highly invasive surgical resection of the liver tumor is the main approach used to eliminate the tumor. Mechanisms that terminate liver regeneration when the liver reaches the original size are not known. The aims of this work were to generate an animal model that fails to stop liver regeneration after surgical resections and elucidate mechanisms that are involved in termination of liver regeneration. Because epigenetic control of liver function has been previously implicated in the regulation of liver proliferation, we generated C/EBPα‐S193A knockin mice, which have alterations in formation of complexes of C/EBP family proteins with chromatin remodeling proteins. The C/EBPα‐S193A mice have altered liver morphology and altered liver function leading to changes of glucose metabolism and blood parameters. Examination of the proliferative capacity of C/EBPα‐S193A livers showed that livers of S193A mice have a higher rate of proliferation after birth, but stop proliferation at the age of 2 months. These animals have increased liver proliferation in response to liver surgery as well as carbon tetrachloride (CCl4)‐mediated injury. Importantly, livers of C/EBPα‐S193A mice fail to stop liver regeneration after surgery when livers reach the original, preresection, size. The failure of S193A livers to stop regeneration correlates with the epigenetic repression of key regulators of liver proliferation C/EBPα, p53, FXR, SIRT1, PGC1α, and TERT by C/EBPβ‐HDAC1 complexes. The C/EBPβ‐HDAC1 complexes also repress promoters of enzymes of glucose synthesis PEPCK and G6Pase. Conclusion: Proper cooperation of C/EBP and chromatin remodeling proteins is essential for the termination of liver regeneration after surgery and for maintenance of liver functions. (Hepatology 2015;61:315–325)